Pengaruh Perencanaan Anggaran dan Pengendalian Intern terhadap Akuntabilitas Publik pada Pemerintah Daerah Provinsi Riau - Agustin, Neli (Akuntansi dan Manajemen, 2019)
This study aims to empirically examine the effect of budget planning and internal control on public accountability in the Riau Provincial Government. This study uses quantitative methods because it emphasizes the method of data analysis with statistical procedures. The type of data used in this study is primary data. Primary data obtained from the distribution of questionnaires distributed by researchers to respondents contained in SKPD of the Regional Government of Riau Province. The research sample is SKPD employees who work in the planning department as well as employees who are the internal audit team at the SKPD in the Riau Provincial Government. The statistical method uses Multiple Linear Regression Analysis. Theresults of this study indicate that budget planning and internal control have a positive and significant effecton public accountability in Riau province